PENGEMBANGAN KOMPETENSI KEPRIBADIAN PENDIDIK PAI ABAD KE-21 - Willy Akmansyah Lubis; Fadriati; Ermis Suryana (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
In Education, teacher is a profession that is given the responsibility to provide knowledge, guide, advise, be a role model and shape the character of students to be even better. This article was prepared to find out and explore in depth the characteristics of 21st century education, its issues and challenges as well as several personality competency development models that provide PAI teachers with a perspective to prepare their personalities in accordance with existing standards and in line with the Shari'a and thoughts. Islamic thought. This paper uses the library research method developed by John Creswell. Through literature analysis, it was found that 21st century education is more about using one's abilities to the maximum accompanied by the existence of technology. There are several challenges that will be faced by PAI teachers, especially those who will be dealing directly with the alpha generation as students. So there are several models for developing a teacher's personality competence, such as training, coaching, workshops, further study, reciting the Koran, religious/spiritual activities, rewards, motivation.